The Congenital Tricuspid Valve Spectrum: From Ebstein to Dysplasia. Issue 6 (November 2020) - Stephens, Elizabeth H.; Dearani, Joseph A.; Qureshi, Muhammad Y.; Ammash, Naser; Maleszewski, Joseph J.
Ebstein anomaly has a breadth of presentations, including "typical" and "atypical, " and can be confused with congenital tricuspid dysplasia. We summarize how to differentiate within this spectrum of disease. Both typical and atypical Ebstein have an underlying failure of delamination, but atypical Ebstein does not have ≥8mm/m 2 apical septal leaflet displacement. In congenital tricuspid dysplasia, delamination is normal, while the leaflets and subvalvar apparatus are abnormal. To summarize, the sine qua non feature of Ebstein anomaly, present in both typical and atypical, is the failure of delamination. These are distinct from congenital tricuspid valve dysplasia in which the pathology is in the leaflet itself.